Organización micro empresarial de los artesanos en el área administrativa que permita el desarrollo socioeconómico del cantón Montalvo, provincia de los Ríos. - Magarsca Naranjo, Daysi Natividad (2014)
The present investigation titled ORGANIZATION MANAGERIAL MICRO OF THE ARTISANS IN THE ADMINISTRATIVE AREA THAT ALLOWS THE SOCIOECONOMIC DEVELOPMENT OF THE CANTON MONTALVO, COUNTY OF THE RIVERS, has for purpose to contribute with this important sector of the society of the canton Montalvo, giving guidelines so that its administration is productive in economic terms. The study is developed in the canton Montalvo, where an organization denominated Association exists Interprofesional of Artisans Montalvinos, which contains people that carry out a without number of activities to produce goods in a handmade way and also the offer of services, among them is: mechanics, painters, cabinetmakers, barbers, tailors, tailors, etc...